Organomineral Fertilizer Is an Agronomic Efficient Alternative for Poultry Litter Phosphorus Recycling in an Acidic Ferralsol - de Melo Benites, Vinicius; Dal Molin, Sulian Junkes; Menezes, June Faria Scherrer; Guimarães, Getúlio Sousa; de Almeida Machado, Pedro Luiz Oliveira (Frontiers in Agronomy, 2022)
Brazil is a large phosphate importer due to the high demand for this nutrient for grain cropping on very weathered soils. However, Brazil has an important poultry production that generates 6.8 million m3 year−1 of organic residue containing phosphorus and other nutrients, increasing the risk of environmental harm. However, if well managed, poultry litter can be a valuable source of P for crop growth in low fertile tropic soils. This article summarizes the long-term agronomic efficiency of organomineral fertilizers in supplying P to soybean and soil P maintenance as a strategy for secondary P recycling. Three fertilizers were used as P source: organomineral based on raw poultry litter, organomineral based on composted poultry litter; and a mineral monoammonium phosphate. Five soybean crop seasons were conducted with annual P doses (20, 40, 60, and 80 kg ha−1 of P2O5) and control without P application. After five crops, one additional soybean crop season was grown without P to evaluate the residual effect. Phosphorus concentration in leaves was evaluated in the first four seasons, and soil P availability in the first, third, and fourth seasons. There was no difference in soybean grain yield, P concentration in leaves, and soil P availability as a function of the P sources in the first crop. Soybean grain yield only varied with the P rate applied after the second season, when the control had the lowest grain yield. After five crops, organomineral resulted in a slight but significant soybean yield gain compared with MAP at higher doses. Over time, the available soil P increased with the highest P dose and decreased in the control treatment. The intermediate dose of 40 kg ha−1 P2O5 was enough to keep soil P level and lead to high soybean grain yield over the time, suggesting that the rate of applied P close to the P exportation by the grains has a long-term sustainable effect even in tropical soils, where residual P stocks are used. It can be concluded that organomineral fertilizer is an efficient farm input that can be used for residue destination and nutrient recycling, especially in acid tropical soils.